2020
DOI: 10.1007/s11612-020-00530-0
|View full text |Cite
|
Sign up to set email alerts
|

Arbeitszeitgestaltung in der digitalisierten Arbeitswelt: Ein systematisches Literatur Review zur Wirkung von Arbeitszeitverkürzung in Bezug auf die psychische Gesundheit

Abstract: Zusammenfassung Dieser Beitrag der Zeitschrift Gruppe. Interaktion. Organisation. (GIO) stellt ein systematisches Review zum Zusammenhang der Arbeitszeitverkürzung (bei vollem Gehalt) und psychischen Gesundheit auf der Grundlage vorhandener Studien vor, um Chancen und Risiken besser einschätzen und beurteilen zu können. Die Diskussion über die Verkürzung von Arbeitszeiten wird nicht zuletzt durch die vielfältigen Möglichkeiten der Digitalisierung der Arbeit verstärkt. Die Literatursuche ergab insgesamt 114 Art… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 32 publications
0
1
0
2
Order By: Relevance
“…Another related discussion concerns the reduction of weekly working days with full wage compensation (i.e., a 4-day week). Having one day free in a week could be considered as having a brief vacation every week and some studies indeed found positive effects on well-being indicators (see reviews of Campbell, 2023; Jansen-Preilowski et al, 2020; Voglino et al, 2022). In 4-day-week schedules, work-related strain accumulation could possibly be reduced by more frequent rest periods (e.g., having a day off in the middle of the week) or more frequent forms of “short vacations” in terms of extended weekends.…”
Section: Discussionmentioning
confidence: 99%
“…Another related discussion concerns the reduction of weekly working days with full wage compensation (i.e., a 4-day week). Having one day free in a week could be considered as having a brief vacation every week and some studies indeed found positive effects on well-being indicators (see reviews of Campbell, 2023; Jansen-Preilowski et al, 2020; Voglino et al, 2022). In 4-day-week schedules, work-related strain accumulation could possibly be reduced by more frequent rest periods (e.g., having a day off in the middle of the week) or more frequent forms of “short vacations” in terms of extended weekends.…”
Section: Discussionmentioning
confidence: 99%
“…e) Arbeitszeitverkürzung kann also -wenn sie nicht in Verdichtung mündet -neben den bekannten positiven Effekten auf die physische Gesundheit (Caruso et al 2004;Kauffeld et al 2004;Wirtz 2012;Jansen-Preilowski et al 2020;Pega et al 2021) ebensolche auf die psychische Gesundheit haben.…”
Section: Arbeitszeitverkürzung Als Katalysator Für Gesellschaftlichen...unclassified
“…• Welche Rolle nehmen Betriebsräte und Betriebsvereinbarungen in der betrieblichen Arbeitszeitgestaltung ein? Aus wissenschaftlicher Perspektive ergibt sich zudem die Notwendigkeit einer Systematisierung der diversen Praktiken, die unter den sehr weiten Begriff von Arbeitszeitverkürzung fallen, sowie der jeweiligen Belastungen und Erleichterungen für die Beschäftigten (Jansen-Preilowski et al 2020). Betriebsfallstudien ermöglichen es, die verschiedenen Perspektiven auf Arbeitszeit einzufangen, und sie können daher ein nuanciertes und facettenreiches Bild liefern, wie auf Ebene der Betriebe kürzere Arbeitszeiten ermöglicht oder eben auch verhindert werden bzw.…”
Section: Forschungszielunclassified